Electrocortical correlates of temperament - Tatalović Vorkapić, Sanja (Array, 2013)
The aim of this study was to investigate the relationship between three temperament dimensions: strength of excitation, strength of inhibition and mobility measured by Pavlov’s Temperament Survey (PTS), and amplitudes and latencies of evoked brain potentials (N1, P2, N2, P3 & SW) measured by a visual oddball paradigm in two blocks. The participants were female psychology students (N=54) with mean age of 20. Significant positive correlations were determined between amplitudes of N1-P2-N2-P3 components and strength of excitation and mobility in the first and second block, mostly on parietal electrodes, as well as significant negative correlations of amplitudes of N1-P2-N2-P3 components and strength of inhibition. Considering measurement limitations important future study directions have been given.